2000
DOI: 10.1103/physrevlett.84.1832
|View full text |Cite
|
Sign up to set email alerts
|

Factorial Moments Analyses Show a Characteristic Length Scale in DNA Sequences

Abstract: A unique feature of most of the DNA sequences, found through the factorial moments analysis, is the existence of a characteristic length scale around which the density distribution is nearly Poissonian. Above this point, the DNA sequences, irrespective of their intron contents, show long range correlations with a significant deviation from the Gaussian statistics, while, below this point, the DNA statistics are essentially Gaussian. The famous DNA walk representation is also shown to be a special case of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 20 publications
1
22
0
Order By: Relevance
“…The results obtained using this method demonstrated that a large number of known genetic texts contain sequences with latent periodicity of various lengths and various types. It is in agreement with the results of investigation of DNA sequences by integral mathematical methods and finding the long-range correlations (LRC) in DNA sequences [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. a -Alpha platelet-derived growth factor receptor precursor [52] from Rattus norvegicus (1088 amino acids, PGDS_RAT in Swiss-prot).…”
Section: Discussionsupporting
confidence: 73%
“…The results obtained using this method demonstrated that a large number of known genetic texts contain sequences with latent periodicity of various lengths and various types. It is in agreement with the results of investigation of DNA sequences by integral mathematical methods and finding the long-range correlations (LRC) in DNA sequences [55][56][57][58][59][60][61][62][63][64][65][66][67][68]. a -Alpha platelet-derived growth factor receptor precursor [52] from Rattus norvegicus (1088 amino acids, PGDS_RAT in Swiss-prot).…”
Section: Discussionsupporting
confidence: 73%
“…The pioneer papers mainly focused on the controversial issue of whether long-range correlations are a property shared by both coding and non-coding sequences or are only present in non-coding sequences [2][3][4][5]. The results of more recent papers [6,7] yield the convincing conclusion that the former condition applies. However, some statistical aspects of the DNA sequences are still obscure, and it is not yet known to what an extent the dynamic approach to DNA sequences proposed by the authors of Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Now, it has been widely used in the analysis of event by event correlations and fluctuations, such as the DNA sequence [29], the hadronic decay [30], and the spectra of complex networks [31], as it allows for a direct access to the dynamical fluctuations of the multiplicity with the function of dismissing the statistical fluctuations due to finite number of events [14]. While applied to the financial systems, it provides a way to analyze the intermittency or the self-similarity behaviors in the dynamics of distribution of the correlation coefficients, despite the limited financial data.…”
Section: Scaled Factorial Moment Methodsmentioning
confidence: 99%